What about the results? Lessons from long-term process support to stre ngthen results-based management (RBM) for Swedish framework NGOs opera ting in Western Balkans - Ørnemark, Charlotte (NCG, 2012)
The observations and lessons outlined in this report should be seen as a contribution to the on-going learning and reflections in a wider de bate on how to assess and monitor results from support to CSOs involve d in complex social change processes (as opposed to those involved in more ‘classical’ service delivery and more linear development assistan ce). These lessons, though directly emerging from the consultancy to p rovide long-term RBM support to the FOs and their local CSO partners i n Western Balkans, also draws on previous experiences and similar less ons from on-going initiatives. In brief, these lessons call for a cert ain ‘paradigm shift’ in the way we (as development professionals) rega rd and support RBM for actors involved in less tangible social change processes in highly contested political spaces. Some of these shifts, outlined in more detail in different sections of this report, are summ arised below: ? From a linear, aggregated cause-and-effect thinking ar ound RBM to one that is linked to human factors and is embedded in sys tems, ? From pushing the burden of reporting down in the system to a c learer division of labour between donors, recipient governments, inter mediary agents like framework NGOs (FOs) and implementing CSOs with ea ch actor using its comparative advantage and appropriate role in the R BM process and for its own learning, ? From operating in programming a nd results frameworks where outcomes and impact are largely assumed to be predictable to setting up systems that deal with uncertainty and t hat capture emerging result patterns through tracking of gradual chang es, ? From a project/programme perspective to a focus on institutions and systems as actors and arenas for change, where organisations are e nabled to act as change agents towards clearly identified processes of social transformation, ? From SMART to REAL results frameworks – alth ough SMART (specific, measurable, achievable, realistic and time-bound ) principles are always good to keep in mind for the formulation of go als and indicators, the danger of coming up with fictive measuring fra meworks calls for a more systematic incorporation of ‘real’ concerns, including making RBM processes rights-based, embedded in local realiti es (and empowering for those involved), aligned to national reform eff orts and national and international human rights commitments, and lear ning-oriented for all different levels of operations.